Aqua regia as a competitive leaching agent for metallic impurity removal from rice husk - Akhter, Faheem; Ahmed Soomro, Suhail; Inglezakis, Vassilis J. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rice husk is widely recognized as significant biomass containing cellulose, lignin and silica. Usually, rice husk is combusted for energy purposes but it contributes to severe environmental pollution. Therefore, the integrated components of rice husk (i.e. silica) can be extracted and converted into value-added products. However, the metallic impurities must be removed before further extraction. Generally, rice husk is leached with conventional acids such as HCl and nitric acid, however, the present study has used aqua regia and compared the results with conventional acids. The leached rice husk samples were characterized using TGA, SEM and EDX. The results of the present work indicate that the aqua regia carries a significant leaching potential to remove metallic impurities from rice husk with 1 M and 2 M solutions removing more than 98% and 99% of impurities respectively. However, its brief chemical stability compels it to be prepared and used immediately.